Co-Treatment of Purified Annatto Oil (Bixa orellana L.) and Its Granules (Chronic®) Improves the Blood Lipid Profile and Bone Protective Effects of Testosterone in the Orchiectomy-Induced Osteoporosis in Wistar Rats - Arlindo César Matias Pereira; Helison de Oliveira Carvalho; Danna Emanuelle Santos Gonçalves; Karyny Roberta Tavares Picanço; Abrahão Victor Tavares de Lima Teixeira dos Santos; Heitor Ribeiro da Silva; Francinaldo Sarges Braga; Roberto Messias Bezerra; Alessandro de Sousa Nunes; Maira Tiyomi Sacata Tongo Nazima; Júlia Gomes Cerqueira; Talisson Taglialegna; et al. (Molecules, 2021)
This study aimed to evaluate and compare the effects of co-treatment with purified annatto oil (PAO) or its granules (GRA, Chronic®) with that of testosterone on the orchiectomy-induced osteoporosis in Wistar rats. After surgery, rats were treated from day 7 until day 45 with testosterone only (TES, 7 mg/kg, IM) or TES + PAO or GRA (200 mg/kg, p.o.). The following parameters were evaluated: food/water intake, weight, HDL, LDL, glucose, triglycerides (TG), total cholesterol (TC), alkaline phosphatase levels, blood phosphorus and calcium contents, femur weight, structure (through scanning electron microscopy), and calcium content (through atomic absorption spectrophotometry). Our results show that orchiectomy could significantly change the blood lipid profile and decrease bone integrity parameters. Testosterone reposition alone could improve some endpoints, including LDL, TC, bone weight, and bone calcium concentration. However, other parameters were not significantly improved. Co-treatment with PAO or GRA improved the blood lipid profile and bone integrity more significantly and improved some endpoints not affected by testosterone reposition alone (such as TG levels and trabeculae sizes). The results suggest that co-treatment with annatto products improved the blood lipid profile and the anti-osteoporosis effects of testosterone. Overall, GRA had better results than PAO.